High-strength, translucent glass-ceramics in the system MgO-ZnO-Al2O3-SiO2-ZrO2. Issue 7 (July 2017) - Seidel, Sabrina; Dittmer, Marc; Höland, Wolfram; Rüssel, Christian
Abstract: In a MgO/Al2 O3 /SiO2 /ZrO2 glass-ceramic MgO was substituted by equimolar ZnO concentrations. The effect of this substitution on the crystallization behavior, the microstructure and the mechanical properties of the glass-ceramics was studied. The crystal phases and the microstructure were analysed by X-ray diffraction and scanning electron microscopy. Tetragonal ZrO2, a high-/low-quartz solid solution (high-/low-QSS) and spinel/gahnite were observed in the entire bulk of the glass-ceramics. Additionally, indialite or cristobalite are detected at the surface of some glass-ceramics. The substitution of small ZnO concentrations induces an increasing low-QSS concentration and hence higher microhardness and Young's modulus. By contrast, higher ZnO concentrations lead to a liquid/liquid phase separation in the glass. Moreover, spinel/gahnite is the main crystal phase and the concentration of the low-QSS is smaller in theses glass-ceramics which also do not show as good mechanical properties. However, the biaxial flexural strength of the glass-ceramics is not notably affected by the ZnO concentration.